The Emergence of Quality Journalism in the Ibero-American Context: a Reading from the Proposal of Pierre Bourdieu - Gayà Morlà, Catalina (2022)
In the current context of financialization and digital metanarrative, a reflection on quality journalism linked to emerging journalistic proposals in Ibero-America is urgently needed. For this reason, this article reviews the work of Pierre Bourdieu on the concepts of field, doxa and habitus and connects them to the current debates in the disciplinary matrix of journalism. The article proposes a necessary distinction between quality journalism and the narrative arising from a financialized media field. The text constitutes a theoretical contribution by articulating Bourdieu’s theories with the debate about quality journalism. Finally, the article discusses the need to consider the role of Communication faculties as drivers of the journalistic field.